2022
DOI: 10.3389/fphar.2022.999115
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and experimental verification-based strategy to explore the underlying mechanism of Liu Jun An Wei formula in the treatment of gastrointestinal reactions caused by chemotherapy for colorectal cancer

Abstract: Background: Liu Jun An Wei formula (LJAW), derived from “Liu Jun Zi Decoction”, is a classical prescription of Tradition Chinese Medicine and has been used for the treatment of gastrointestinal reactions caused by chemotherapy for colorectal cancer (CRC) for many years. Its molecular mechanism remains to be further explored.Objective: To clarify the mechanism of LJAW in attenuating gastrointestinal reactions caused by chemotherapy for CRC.Methods: The 5-fluorouracil (5-FU) induced mouse and intestine organoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Thereby, novel drugs developed with specific ingredients greatly improve clinical efficacy and reduce toxicity and side effect. For example, the underlying mechanism of Liu Jun An Wei formula in treating gastrointestinal reactions caused by chemotherapy for colorectal cancer is explored by network pharmacology ( 38 ). Besides, He et al revealed that Danshen promoted JAL-STAT signaling pathway to treat anemia according to network pharmacology ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, novel drugs developed with specific ingredients greatly improve clinical efficacy and reduce toxicity and side effect. For example, the underlying mechanism of Liu Jun An Wei formula in treating gastrointestinal reactions caused by chemotherapy for colorectal cancer is explored by network pharmacology ( 38 ). Besides, He et al revealed that Danshen promoted JAL-STAT signaling pathway to treat anemia according to network pharmacology ( 39 ).…”
Section: Discussionmentioning
confidence: 99%